Targeting the Opioid Pathway for Uremic Pruritus: A Systematic Review and Meta-analysis. Issue 1 (7th December 2016) - Jaiswal, Deep; Uzans, Drea; Hayden, Jill; Kiberd, Bryce A.; Tennankore, Karthik K.
Background: Patients undergoing hemodialysis or peritoneal dialysis often experience pruritus which is associated with morbidity and mortality. One proposed treatment approach is to target the opioid pathway using either µ-opioid antagonists or κ-opioid agonists. Objective: To review the efficacy of targeting the opioid pathway for pruritus among dialysis patients (uremic pruritus). Design: Systematic review and meta-analysis. Setting/Methods: The systematic review included randomized controlled and randomized crossover trials identified in the MEDLINE, EMBASE, and Cochrane databases (1990 to June 2014) evaluating the efficacy of µ-opioid antagonists or κ-opioid agonists in the treatment of uremic pruritus. Patients: Adult (≥18 years) chronic dialysis patients. Measurements: The primary outcome being evaluated was reduction in itch severity measured on a patient-reported visual analog scale (VAS). Results: Five studies out of 3587 screened articles met the inclusion criteria. Three studies evaluated the efficacy of naltrexone, a µ-opioid antagonist, and 2 studies evaluated the efficacy of nalfurafine, a κ-opioid agonist. Duration of included studies was short, ranging from 2 to 9 weeks. Limitations: Due to the heterogeneity in reporting of outcomes, data from the studies evaluating naltrexone could not be pooled. Pooled analysis, using a random effects model, found that use of nalfurafine resulted in a 9.50 mm (95% confidence interval [CI], 6.27-12.74, P < .001) greater reduction of itch severity (measured on a 100-mm VAS) than placebo in the treatment of uremic pruritus. Conclusions: Nalfurafine holds some promise with respect to the treatment of uremic pruritus among dialysis patients. However, more long-term randomized controlled trials evaluating the efficacy of therapies targeting the opioid pathway for uremic pruritus are required.